Alginate Lyases: Sources, Mechanism of Activity and Potencial Application - Subaryono Subaryono; Rosmawaty Peranginangin; Maggy Thenawidjaja Suhartono; Fransiska Rungkat Zakaria (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2013)
Alginate lyases are group of enzymes which catalyze depolymerization of alginate into oligosaccharides. Alginate lyase have been widely used in many applications such as in production of bioactive oligosaccharides, control of polysaccharide rheological properties, and polysaccharide structure analysis. The products of alginate lyase, polysaccharide structure analysis, alginate oligosaccharides (AOS) have many biological activities including act as prebiotics, immune modulator, anticoagulation, antioxidant, anticancer, growth promoting activities, promote production of antibiotics and ethanol. In relation to the importance of alginate lyases, their potential aplications and prospect in development of new bioactive products, we present review of the enzymes, sources, mechanism of activity and potential applications. This paper also discussed some new biological engineering in alginate lyase production.